PENGARUH GAYA KEPEMIMPINAN KEPALA DESA, BUDAYA DAERAH DAN PENGETAHUAN PERPAJAKAN MASYARAKAT DESA TERHADAP KEPATUHAN MASYARAKAT DESA MEMBAYAR PAJAK BUMI DAN BANGUNAN DI DESA NGAWEN KECAMATAN SIDAYU - Roudhotus Sholihah; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2021)
Roudhotus Sholihah. The Influence of Village Head Leadership Style, Regional Culture and Tax Knowledge of Village Communities on Village Community Compliance in Paying Land and Building Taxes in Ngawen Village, Sidayu District, Gresik Regency. The objectives of this study were a.) To analyze the influence of the leadership style of the village head, local culture and tax knowledge that affect the compliance of the village community b.) To analyze the influence of the leadership style of the village head on the obedience of the village community. c.) to analyze the influence of regional culture on the compliance of the village community. d.) to analyze the influence of tax knowledge on village community compliance. The data collection method applies a questionnaire and the data analysis method applied in this research is descriptive statistical analysis, research instruments, normality, classical assumptions, multiple linear regression analysis, and hypotheses. From the results obtained by the researcher, it can be proven that there is an influence of the leadership style variable of the Village Head through simultaneous or partial compliance with the villagers paying PBB in Ngawen Sidayu Gresik Village, and for regional cultural variables through simultaneous or partial influence there is an influence with the obedience of the village community to pay PBB in the village. Ngawen Sidayu Gresik, then the variable knowledge of taxation through simultaneous or partial influences has an effect on the obedience of the villagers paying PBB in Ngawen Sidayu Gresik Village.Keywords: Village Head Leadership Style, Regional Culture, and Tax Knowledge, Village Community Compliance.